2021
DOI: 10.1016/j.numecd.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent and continuous caloric restriction on Sirtuin1 concentration depends on sex and body mass index

Abstract: Background & aims: The favorable effect of caloric restriction (CR) on health span is well known and partly mediated by the sirtuin system. Sirtuin1, a regulator of energy homeostasis in response to nutrient availability, is activated by CR. We therefore investigated effects of two different CR regimens on Sirtuin1 concentrations. Methods & results: The study included 112 abdominally obese subjects, randomized to intermittent or continuous CR for 1 year. Blood samples and anthropometric measures were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…One study 13 from a previous report was added to the remaining 25 records. 14 - 38 Among the selected 26 articles, one trial with patients with type 1 diabetes mellitus 23 reported most of the targeted outcomes as medians and ranges without variances; therefore, we excluded it from our calculation of integrated mean differences (MDs) because of the unfeasibility of calculating the standard deviation (SD) from the given data. In the end, we included 16 RCTs from 25 articles comprising 1,438 participants in this meta-analysis ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…One study 13 from a previous report was added to the remaining 25 records. 14 - 38 Among the selected 26 articles, one trial with patients with type 1 diabetes mellitus 23 reported most of the targeted outcomes as medians and ranges without variances; therefore, we excluded it from our calculation of integrated mean differences (MDs) because of the unfeasibility of calculating the standard deviation (SD) from the given data. In the end, we included 16 RCTs from 25 articles comprising 1,438 participants in this meta-analysis ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Our results also showed a positive association between changes in Sirt-1 and BMI. This association is poorly understood, but a previous study showed similar results in women [ 29 ].…”
Section: Discussionmentioning
confidence: 93%
“…Irrespective of the duration of the intervention (short term [4-12 weeks] or long term [24-102 weeks]), weight loss with ADF and 5:2 fasting was comparable to that achieved by calorie restriction (CR). 10,14,15,[25][26][27][28][29][30][31][32][33][34] Meanwhile, weight loss with TRE alone (1%-5% decrease from baseline over 8-12 weeks) 23,35,36 was not superior to that achieved with CR and was less than that observed with ADF or 5:2 fasting unless total calorie intake was restricted along with TRE. Thus, long-term TRE combined with an appropriate energy-restricted diet can enhance weight loss, but this is mainly attributed to CR.…”
Section: Time-restricted Eating (Tre)mentioning
confidence: 86%